Uncovering latent profiles of political news consumers and their associations with political views and their extremity - Cornelia Sindermann (Discover Psychology)
Abstract In today's high-choice media environment, the relations between news consumption and (extreme) political views receive extensive attention. While social media and news aggregators are often blamed for political polarization, theories from media psychology highlight the importance of additional aspects of news consumption, aside from the media types used, in impacting the formation of political views and thereby, for instance, polarization. However, these aspects are typically studied in isolation, neglecting the heterogeneity in where and how news can be consumed. Based on this observation, the present work investigated the conjoint relations of various aspects of news consumption across media types with political views and their extremity. Study 1 included two samples of N = 714 (sample 1) and N = 721 (sample 2) participants completing an online survey assessing political news consumption habits and general political views, namely, ideology and affective polarization. Study 2 included two samples of N = 725 (sample 3) and N = 713 (sample 4) participants completing scales on issue-specific political views, namely, attitudes on war and the war against Ukraine. Latent Profile Analyses revealed four mostly media type-specific news consumer profiles replicated across samples, indicating that individuals choose one media type, like social media, aggregators, or print media, and devote considerable time to consuming political news from various sources, including attitude-incongruent news and diverse perspectives, from the same selected media type. While these profiles differed on sociodemographic and personality variables, few significant relations were found between these profiles and political views. These findings highlight the complexity of these relations and challenge the assumption that only certain media types, and news consumption via them, drive political extremity.